Chlorinated Isoprene Rubbers in Adhesive Composites. (May 2017) - Zuev, A.A.; Lyusova, L.R.; Boreiko, N.P.
Now there is not a single area of industry that can do without adhesive elastomer materials. Composites based on synthetic rubbers comprise 75% of the total volume of adhesive materials produced, which is due to the combination of unique properties typical of the elastomer base of the adhesive. The base of many imported adhesives for the bonding of rubber to metal is chlorinated natural rubber. As an alternative, chlorinated synthetic isoprene rubber has been proposed, developed at the Scientific Research Institute for Synthetic Rubber in St Petersburg. The chlorinated isoprene rubber was compared with imported chlorinated natural rubber in adhesive composites, and the physicomechanical properties of mixes based on a blend of chlorinated rubber and nitrile butadiene rubber were investigated. The investigation was conducted on chlorinated natural rubber of grade Pergut S20, chlorinated isoprene rubber SKI-3, and nitrile butadiene rubbers of grades BNKS-28AMN and SKN-26S. The influence of the ratio of chlorinated rubber to nitrile butadiene rubber and the technological factors of mix preparation on the properties of films produced from them was established. It was shown that, in terms of the level of properties, home-produced chlorinated rubber can be used as the base for adhesives for hot bonding of rubber to metal instead of imported Pergut S20.